Marketing Behavior of Certified Organic Farmers in Tamil Nadu - Sivaraj, Paramasivam; Philip, Henry; Venkata Pirabu, Jegadeesan (Journal of Extension Education, 2019)
A study was conducted to assess the marketing behavior of organic Farmers. Ex post facto research design was used in this study. The study was conducted in Coimbatore, Erode and Tiruppur districts of Tamil Nadu. Three blocks were selected purposively and a sample of 20 certified organic farmers were selected from each of the blocks purposively. A total of 180 certified organic farmers were surveyed for the study. Three fourths of the certified organic farmers fell under the fully selling pattern of organic produce, and 38.89 per cent of the certified organic farmers sell the entire produce immediately after the harvest.